Change in body mass index during transition to statutory retirement: an occupational cohort study - Stenholm S; Solovieva S; Viikari-Juntura E; Aalto V; Kivimäki M; Vahtera J (BIOMED CENTRAL LTD, 2022)
Background: Retirement is a major life transition affecting health behaviors. The aim of this study was to examine within-individual changes in body mass index (BMI) during transition from full-time work to statutory retirement by sex and physical work characteristics.Methods: A multiwave cohort study repeated every 4 years and data linkage to records from retirement registers. Participants were 5426 Finnish public-sector employees who retired on a statutory basis in 2000-2011 and who reported their body weight one to three times prior to (w(-3), w(-2), w(-1)), and one to three times after (w(+1), w(+2), w(+3)) retirement.Results: During the 4-year retirement transition (w(+1), vs. w(-1)) men showed decline in BMI, which was most marked among men with sedentary work (-0.18 kg/m(2), 95% CI -.30 to -0.05). In contrast, BMI increased during retirement transition in women and was most marked among women with diverse (0.14 kg/m(2), 95% CI 0.08 to 0.20) or physically heavy work (0.31 kg/m(2), 95% CI 0.16 to 0.45). Physical activity during leisure time or commuting to work, alcohol consumption or smoking did not explain the observed changes during retirement transition.Conclusions: In this study statutory retirement was associated with small changes in BMI. Weight loss was most visible in men retiring from sedentary jobs and weight gain in women retiring from diverse and physically heavy jobs.